Laying the groundwork for socialisation and knowledge construction within 3D virtual worlds - Shailey Minocha; Dave Roberts (Association for Learning Technology, 2008)
The paper reports the theoretical underpinnings for the pedagogical role and rationale for adopting 3D virtual worlds for socialisation and knowledge creation in distance education. Socialisation or ‘knowing one another' in remote distributed environments can be achieved through synchronous technologies such as instant messaging, audio and video-conferencing. However, a 3D virtual world can provide an immersive experience where there is a visual presence and virtual proximity of the group members in terms of their 3D selves (avatars). We discuss the affordances of a 3D virtual world and its role in providing a platform for pedagogical design that engenders socialisation, synchronous communication and collaboration. We propose the use of a knowledge construction model as a framework for guiding the design of collaborative activities in a 3D virtual world for blended learning environments. We believe that this framework will also be useful for integrating 2D environments such as blogs, wikis and forums with a 3D learning environment. We consider the implications of this in the context of blended learning in distance education. This paper would be of interest to course designers, researchers, teachers, staff developers and policy-makers who are involved in integrating 3D virtual worlds within the curriculum of their programmes and institutions.